ANALISIS PENGARUH KUALITAS PELAYANAN TERHADAP KEPUASAN PENGUNJUNG AGROEDUWISATA ORGANIK MULYAHARJA - Siti Aminatu Zuhria; Lisa Ratnasari; Farhat Umar (Departmen of Agribusiness, Economics and Management Faculty, Bogor Agricultural University, 2026)
The development of the agricultural sector into agro-tourism combined with education is widely known as agro-edutourism. Agroeduwisata Organik Mulyaharja provided various facilities, facilities and infrastructure as well as organic farming educational packages. Visitors were a measure of the success and sustainability of business in the tourism sector. The number of visitors to Agroeduwisata Organik Mulyaharja still fluctuates every month. Consumer satisfaction with service was an important factor that needs attention. This study aimed to analyze visitor satisfaction with service quality including physical evidence, reliability, responsiveness, assurance, and care provided by Agroeduwisata Organik Mulyaharja. The research used a case study method with a sample size of 100 respondents. The sampling method used purposive sampling technique. Scale of measurement using a likert scale. Methods of data analysis using the customer satisfaction index (CSI), gap analysis (gap), and importance performance analysis (IPA). The results of the analysis showed that the CSI value was 78,64%, meaning that overall visitors were satisfied with the service performance at Agroeduwisata Organik Mulyaharja. The result of the gap analysis showed that the value (performance < expectations) was 3,41 < 3,93 with an average gap of -0,53. Based on these results, it showed that the services at Agroeduwisata Organik Mulyaharja have not fulfilled the wishes of visitors. The result of the IPA analysis showed that the attribute that was the main priority for improving Agroeduwisata Organik Mulyaharja was ease of transportation access to tourist location.